2003
DOI: 10.1542/peds.112.5.e404
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Response Study of OROS Methylphenidate in Children With Attention-Deficit/Hyperactivity Disorder

Abstract: ABSTRACT. Objective. OROS methylphenidate HCL (MPH) is a recently developed long-acting stimulant medication used to treat attention-deficit/hyperactivity disorder (ADHD). This study was conducted to examine dosage effects on ADHD symptoms and stimulant side effects and to explore potential moderating effects of ADHD subtype.Methods. Children with ADHD combined type (ADHD-CT) or predominantly inattentive type (ADHD-PI; n ‫؍‬ 47), ages 5 to 16 years, underwent a placebocontrolled, crossover trial using forced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
183
3
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(207 citation statements)
references
References 42 publications
17
183
3
4
Order By: Relevance
“…All participants completed a semistructured diagnostic interview conducted with the parents and child by a child and adolescent psychiatrist or psychologist (HALP diagnostic interview available from senior author), and met DSM-IV criteria for ADHD based upon the interview and a 'best estimate' diagnosis based upon a standardized 4-6 h evaluation. Diagnostic procedures and subjects are described in more detail in a previous paper (Stein et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants completed a semistructured diagnostic interview conducted with the parents and child by a child and adolescent psychiatrist or psychologist (HALP diagnostic interview available from senior author), and met DSM-IV criteria for ADHD based upon the interview and a 'best estimate' diagnosis based upon a standardized 4-6 h evaluation. Diagnostic procedures and subjects are described in more detail in a previous paper (Stein et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…MPH-and amphetamine (AMP)-based stimulant medications are the most common medical treatments for ADHD (Elia et al, 1999;Conners, 2002), and at low to moderate dosage levels, there is generally an inverse linear doseresponse effect on ADHD symptoms (eg Douglas et al, 1986;Stein et al, 2003). In this paper, we report the results of a prospective, placebo-controlled study of DAT1 genotypes and dose-related MPH response.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical results from the other studies were less clearly presented (see Appendix 12), although Stein and colleagues 92 reported that as the ER-MPH dose was increased from 0 to 54 mg, parentrated ADHD symptoms decreased in a linear manner ( p < 0.001).…”
Section: [Confidential Information Removed]mentioning
confidence: 95%
“…The other study in this category measured other behavioural outcomes using scales such as the ADHD Rating Scale IV. 92 Details from these results are presented in Appendix 12. …”
Section: Er-mph Low Dose (յ20 Mg/day) Versus Placebomentioning
confidence: 99%
See 1 more Smart Citation